KOMPRESI DATA CITRA EFISIENSI PENYIMPANAN DAN PENGIRIMAN PADA MEDIA KOMUNIKASI MOBILE - Kartini, Kartini (Lembaga Penerbitan Universitas Esa Unggul, 2019)
In data communication between work networks, especially image data or image files, messages sent are often of very large size so that sending time is long, as a result the network becomes busier, it can even result in corrupted image data, as well as in image data storage or large image files take up large storage space. Both of these problems can be overcome by encoding the message or the contents of the archive as short as possible, so the message delivery time is also relatively fast, and the storage space required is also small. This method of coding is called data compression or compression. In this study the Run Length Encoding Method is used for compression or compression of image or image data. The study was conducted using the literature study method, testing the type of sample data and making comparison tables. The results obtained provide input regarding the implementation of Image Data Compression (Image) applications and contribute to computer network, internet, intranet or extranet users in sending image data, both for personal and organizational needs. The final results of this study, the size of the image file or image can be reduced to 95.23% of the actual size (can be seen in table 1). Keywords: compression, decompression, image data, Ã‚Â Run Length Encoding